2003
DOI: 10.1159/000071816
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Modulates the Effects of Gastric Injury in Rats: Role of Prostaglandins and Nitric Oxide

Abstract: Experimental evidence has been presented connecting melatonin with the prevention or treatment of gastrointestinal disorders either by the scavenging properties of active oxygen or by receptor-mediated stimulation of gene expression of neutralizing enzymes. Prostaglandins and nitric oxide are important neuroimmunomodulators in digestive physiology and different studies have indicated that the protective properties of melatonin may be explained by prostaglandin and/or nitric oxide mechanisms. The aim of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Although various studies have suggested that melatonin suppresses COX‐2 expression [34–36], a few studies have proposed on the contrary. The study by Kato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies have suggested that melatonin suppresses COX‐2 expression [34–36], a few studies have proposed on the contrary. The study by Kato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Successful ovulation requires elevated follicular prostaglandin E 2 levels. Melatonin treatment (20 mg/kg body weight) significantly increases prostaglandin E 2 concentrations in rat gastric mucosa (98), and melatonin (20 mg/kg body weight intraperitoneal injection) also increases prostaglandin E 2 in rat esophageal tissue (99). On the contrary, physiological concentrations of melatonin inhibit the norepinephrine-induced activation of prostaglandin E 2 in rat medial basal hypothalamus (100).…”
Section: Melatonin and Ovulationmentioning
confidence: 99%
“…In the stomach, melatonin was found to inhibit acid secretion [6,7], and it induces duodenal HCO 3 -secretion in response to gastric acid [8]. Studies in animals showed that melatonin stimulates pancreatic enzyme secretion and improves the outcome of experimental pancreatitis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%